The science of nutrition - Thompson, Janice, 1962-; Manore, Melinda, 1951-; Vaughan, Linda A. (Linda Ann) (Boston : Pearson, 2014)
The Science of Nutrition, Third Edition offers the best combination of text and media to help students master the toughest nutrition concepts in the course, while providing the richest support to save instructors time. This thoroughly current, research-based nutrition text is uniquely organized around the highly regarded applied approach, which organizes vitamins and minerals based on their functions within the body and is easily seen in the organization of the micronutrient (vitamin and mineral) chapters. Rather than requiring rote memorization, the authors present the micronutrients based on their functions (such as fluid and electrolyte balance, antioxidant function, bone health, energy metabolism, and blood health and immunity), so that students can fully understand their effects on the body.
The science of nutrition: linking food, function, and health -- Designing a healthful diet -- The human body: are we really what we eat? -- Carbohydrates: plant-derived energy nutrients -- Lipids: essential energy-supplying nutrients -- Proteins: crucial components of all body tissues -- Metabolism: from food to life -- Nutrients involved in energy metabolism -- Nutrients involved in fluid and electrolyte balance -- Nutrients involved in antioxidant function and vision -- Nutrients involved in bone health -- Nutrients involved in blood health and immunity -- Achieving and maintaining a healthful body weight -- Nutrition and physical activity: keys to good health -- Consumer issues: food safety, production, and impact on the environment -- Nutrition through the life cycle: pregnancy and the first year of life -- Nutrition through the life cycle: childhood and adolescence -- Nutrition through the life cycle: the later years -- Global nutrition.
Includes bibliographical references and index.
Keywords: Nutrition -- Textbooks